Pengembangan Instrumen Tes Esai untuk Mengukur Model Mental Peserta Didik pada Materi Ikatan Kimia - Sofia Fadila; Dwi Finna Syolendra (MASALIQ, 2026)
As abstract subject matter, chemical bonding requires an understanding of submicroscopic concepts that cannot be observed directly, thereby potentially causing misconceptions among students. This understanding can be examined through mental models; however, instruments specifically designed to measure them in chemical bonding topics remain limited. This study aims to produce a valid essay test instrument for measuring students’ mental models in chemical bonding topics. This study used the Plomp development model up to the prototype III stage. Instrument validity was analyzed using Aiken’s V formula with the validity criterion of V ≥ 0.9. The study was conducted at the Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, involving three Chemistry lecturers from the Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, as expert validators, two senior high school chemistry teachers at the needs analysis stage, and six Grade XI students of SMAN 14 Padang at the individual evaluation stage. The results showed an average Aiken’s V value of 0.93, with details of 0.91 for the content component, 0.91 for the construct component, and 0.97 for the language component, all of which were categorized as valid. At the individual evaluation stage, six students gave an average score of 4.26 out of 5.00, or 85%, indicating a highly positive response. The developed instrument integrates three levels of chemical representation, namely macroscopic, submicroscopic, and symbolic, and is equipped with a scoring rubric based on three categories of mental models, namely Scientific Model, Synthesis Model, and Initial Model. The conclusion of this study confirms that the developed essay test instrument is valid for measuring students’ mental models in chemical bonding topics. These findings contribute to the development of chemistry assessment instruments oriented toward conceptual understanding and can be used as a basis for evaluating learning in abstract subject matter.